A Maternal High Fat Diet Leads to Sex-Specific Programming of Mechanical Properties in Supraspinatus Tendons of Adult Rat Offspring - Bolam, Scott M.; Satokar, Vidit V.; Konar, Subhajit; Coleman, Brendan; Monk, Andrew Paul; Cornish, Jillian; Munro, Jacob T.; Vickers, Mark H.; Albert, Benjamin B.; Musson, David S. (Frontiers in Nutrition, 2021)
Background: Over half of women of reproductive age are now overweight or obese. The impact of maternal high-fat diet (HFD) is emerging as an important factor in the development and health of musculoskeletal tissues in offspring, however there is a paucity of evidence examining its effects on tendon. Alterations in the early life environment during critical periods of tendon growth therefore have the potential to influence tendon health that cross the lifespan. We hypothesised that a maternal HFD would alter biomechanical, morphological and gene expression profiles of adult offspring rotator cuff tendon. Materials and Methods: Female Sprague Dawley rats were randomly assigned to either: control diet (CD; 10% kcal from fat) or HFD (45% kcal from fat) 14 days prior to mating and throughout pregnancy and lactation. Eight female and male offspring from each maternal diet group were weaned onto a standard chow diet and then culled at postnatal day 100 for tissue collection. Supraspinatus tendons were used for mechanical testing and histological assessment (cellularity, fibre organization, nuclei shape) and tail tendons were collected for gene expression analysis. Results: A maternal HFD increased the elasticity (Young’s Modulus) in the supraspinatus tendon of male offspring. Female offspring tendon biomechanical properties were not affected by maternal HFD. Gene expression of scleraxis and type I collagen were reduced in male and female offspring of maternal HFD, respectively. Despite this, tendon histological organisation were similar between maternal diet groups in both sexes. Conclusion: An obesogenic diet during pregnancy increased tendon elasticity in male, but not female, offspring. This is the first study to demonstrate that maternal diet can modulate the biomechanical properties of offspring tendon. A maternal HFD may be an important factor in regulating adult offspring tendon homeostasis that may predispose offspring to developing tendinopathies and adverse tendon outcomes in later life.